Pendayagunaan Zakat Mal dalam Mengentaskan Kemiskinan (Study kasus Mustahiq kelurahan Batua kecamatan Manggala kota Makassar) - Syarifudin Syarifudin (Universitas Alma Ata, 2018)
This study aims to determine the use of zakat mal (productive and commercial) influence on poverty alleviation in Kelurahan Batua, Manggala District, Makassar City.The research method used is descriptive quantitative research methods with econometric and Syar'i approaches. The sample used in this study were 100 respondents and this data was analyzed using chi-square test analysis and crostab analysis. The results of the chi-square test results show that 0,000 is greater than the significance level of α = 0.05, this shows that there is an effect of productive and com- mercial zakat utilization on poverty alleviation. The value of P (Risk) is 13.167%, this means that mustahiq which utilizes its zakat on target is likely to increase its welfare by 13.167%. Suggestions for BAZNAS of South Sulawesi Province should focus the program on one area that is favored to alleviate poverty through the empowerment of the community's economy so that the visible results of the utilization of zakat funds are visible.Keywords: Utilization, Zakat Mal, Proverty